2023
DOI: 10.3390/agronomy13092386
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Reconstruction of Nutrient Changes of Quaternary Red Soils (Luvisols) Affected by Land-Use Patterns

Ying-Ying Jiang,
Zhong-Xiu Sun,
Ruo-Meng Wang
et al.

Abstract: The Quaternary red soil widely distributed in China is an important arable land resource. A quantitative understanding of nutrient changes of Quaternary red soils under different land-use patterns is the necessary premise for effective regulation, management, and sustainable utilization. In this study, five typical Quaternary red soil profiles under different land-use patterns were taken as the research object in Chaoyang City, Liaoning Province, China. The results showed that: (1) Buried Quaternary red soils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Jiang et al took quaternary red soils under different land use patterns as the research object and quantitatively analyzed the evolution characteristics of soil nutrients, thus providing an important reference for selecting and optimizing land use patterns and improving soil productivity and management levels. Nutrient change is related to vegetation type, coverage rate, fertilization method, and species [14]. In addition, based on the Cornell Soil Health Assessment system, the authors established a quaternary red soil health evaluation system and found that land use patterns had significant effects on soil health.…”
mentioning
confidence: 99%
“…Jiang et al took quaternary red soils under different land use patterns as the research object and quantitatively analyzed the evolution characteristics of soil nutrients, thus providing an important reference for selecting and optimizing land use patterns and improving soil productivity and management levels. Nutrient change is related to vegetation type, coverage rate, fertilization method, and species [14]. In addition, based on the Cornell Soil Health Assessment system, the authors established a quaternary red soil health evaluation system and found that land use patterns had significant effects on soil health.…”
mentioning
confidence: 99%